The Relationship between Socio-Culture and Family Support with the Status of Complete Basic Immunization in Children in the Working Area of Handil Baru Health Center 2023 - Nidya Safitri; Andi Parellangi; Nursari Abdul Syukur (PT FORMOSA CENDEKIA GLOBAL, 2023)
The target for achieving complete basic immunization at the Handil Baru Health Center in 2021 is 51.78%, with 450 children aged 1 year. Mothers with children aged 1 year are of the opinion that children do not get complete immunizations because the specified time has passed, the child is sick and afraid that the child will have a fever when given immunizations. The aim is to find out the relationship between socio-cultural and family support with complete basic immunization status in children. This type of research is an analytic survey using a cross-sectional design. The population is mothers who have children aged 1 year at the working area Handil Baru Health Center in 2021 adding up to 450 individuals, utilizing the Slovin recipe an example of 82 individuals is gotten. Simple random sampling and proportional random sampling are used in the sampling process. Chi-Square analysis of the data. Most of the respondents were aged between 20-35 years (97.6%), graduated from high school (56.1%) and worked as housewives (46.3%). Socio-cultural conditions were mostly good (61%), family support was balanced (50%) and complete basic immunization status was mostly incomplete (58.5%). There is a socio-cultural relationship with complete basic immunization status (p value : 0.008 < α : 0.05) and there is a relationship between family support and complete basic immunization status (p value : 0.014 < α : 0.05)